HERITABILITAS BOBOT TELUR, BOBOT TETAS DAN BOBOT BADAN AYAM HASIL PERSILANGAN UMUR 1 MINGGU (DOC) - Masili, septtiyanti; Dako, Safriyanto (Jambura Journal of Animal Science, 2018)
The aim was to determine the heritability of egg weight, hatch weight, age of a week body weight in crossbred chickens. This research was conducted from August-November 2017, in Tumbihe Village, Kabila District, Bone Bolango District, Gorontalo Province. The research material was eggs and DOC originating from a cross between male Kampung chicken and female Leghorn chicken, Isa Brown strain, these eggs were weighed and hatched in a hatchery machine. The parameters measured were egg weight heritability, hatch weight, 1 week body weight in crossbred chickens. Data were analyzed by descriptive statistics. The results of this study are the heritability of egg weight in the population is 0.53 ± 0.03 and the variance coefficient is 6.16%. The heritability of hatch weight in the population is 0.53 ± 0.02 and the variance coefficient is 4.33%. While the heritability value of 1 week age weight in the population is 0.53 ± 0.02 and the variance coefficient is 3.26%.